The power of creative expression-On the example of Erkin Vakhidovs epics - Adizova Nilufar Istamovna (Zien Journals, 2022)
Hero of Uzbekistan honored poet of the Uzbek Erkin Vahidov is a creator who has won the hearts of the people with his deep thought philosophical observation and eloquence.